2010
DOI: 10.1007/s00193-010-0291-x
|View full text |Cite
|
Sign up to set email alerts
|

Ignition during hydrogen release from high pressure into the atmosphere

Abstract: The first investigations concerned with a problem of hydrogen jet ignition, during outflow from a high-pressure vessel were carried out nearly 40 years ago by Wolanski and Wojcicki. The research resulted from a dramatic accident in the Chorzow Chemical Plant Azoty, where the explosion of a synthesis gas made up of a mixture composed of three moles of hydrogen per mole of nitrogen, at 300 • C and 30 MPa killed four people. Initial investigation had excluded potential external ignition sources and the main aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 3 publications
(9 reference statements)
1
7
0
Order By: Relevance
“…One of the possible reasons for this stochastic ignition feature is different membrane breaking process which affects the initial turbulence conditions of the flow. Similar behaviour has already been recorded by several researchers [3,4,6,8,9]. It was also observed that for burst pressures up to 16.0 MPa and 25 mm tube length, ignition did not occur for any investigated diameter.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…One of the possible reasons for this stochastic ignition feature is different membrane breaking process which affects the initial turbulence conditions of the flow. Similar behaviour has already been recorded by several researchers [3,4,6,8,9]. It was also observed that for burst pressures up to 16.0 MPa and 25 mm tube length, ignition did not occur for any investigated diameter.…”
Section: Resultssupporting
confidence: 85%
“…The comparison between the present and previously performed works [4,6,9,11,12] for pure hydrogen flow ignition is presented in Fig. 10.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…In recent years one could observe an increased interest in hydrogen technologies and safety issues corresponding to them, including uncontrolled ignition during discharge into the air from high-pressure installations. Latest experimental [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] as well numerical [19][20][21][22][23][24] works focus mainly on the detailed description of the self-ignition mechanism according to different initial and boundary conditions including: extension channel geometry: diameter [4][5][6][7]19], length [5][6][7][8][9][10][11][12][13][14][15][16][17][20][21][22], cross-section shape [7,8,18,23] or obstacle presence in front of the hydrogen stream [18,…”
Section: Introductionmentioning
confidence: 99%
“…However, the results obtained by the researchers using the same experimental stands but applying different geometrical configurations (i.e. Mogi et al [4,10], Oleszczak and Wolanski [7]) group in particular diagram areas. There could be no clear quantitative conclusion regarding extension tube cross-section shape (rectangular or circular) or tube diameter influence on the selfignition propensity.…”
Section: Introductionmentioning
confidence: 99%